1995
DOI: 10.1002/1098-2337(1995)21:6<451::aid-ab2480210605>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Force and dominance in the agonistic behavior of the freshwater crabPotamon fluviatile

Abstract: In decapods, no analysis has ever been conducted of the force exerted by chelae, and the role that strength plays in the establishment of hierarchies. For this purpose, a device was designed to measure the force produced by the major chela in the freshwater crab Potamon fluviatile, where dominance hierarchy and agonistic behavioral patterns have previously been analyzed. Experiments showed that only in the females is strength the main factor influencing the outcome of contests. In males chela size more than ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In addition to foundation species structure, crab morphology impacted ritualized aggression interactions and their outcomes ( Figure 4). As has been observed in numerous species [27,35,36], larger individuals and those with larger weaponry (claws) were more likely to win interactions. Increases in size and relative claw sizes were also associated with costlier behavioral steps (i.e., less shield posture, more display), while decreasing differences in relative claw size increased the likelihood that a competitor would fall in the water.…”
Section: Discussionsupporting
confidence: 63%
“…In addition to foundation species structure, crab morphology impacted ritualized aggression interactions and their outcomes ( Figure 4). As has been observed in numerous species [27,35,36], larger individuals and those with larger weaponry (claws) were more likely to win interactions. Increases in size and relative claw sizes were also associated with costlier behavioral steps (i.e., less shield posture, more display), while decreasing differences in relative claw size increased the likelihood that a competitor would fall in the water.…”
Section: Discussionsupporting
confidence: 63%
“…This finding is based on the assumption that the extensor muscle occupies most of the space in this unit of the appendage, which we observed through dissections in this and other studies. The muscle physiology may vary within the constraints of the available space (Taylor 2001), but many studies on crab claws have shown that shape of the claw is a good proxy for muscle force (Blundon 1988; Lee 1993; Gabbanini et al 1995; Levinton et al 1995; Block and Rebach 1998; Schenk and Wainwright 2001; Taylor 2001; Mitchell et al 2003; Claverie and Smith 2007). Although a more rigorous evaluation of muscle performance in relation to size would be needed, we can reasonably assume that muscle force increases proportionally to muscle shape and size, as seen in other crustaceans (Mitchell et al 2003; Claverie and Smith 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the assessment of an opponent's strength may be crucial in making strategic decisions in this species and may enable crabs to decide whether or not to escalate since the behaviour of winners and losers is very different from an early stage in shore crab ®ghts (Sneddon et al, 1997b). This agrees with research carried out on the freshwater crab Potamon¯uviatile, in which claw strength was important in the establishment of dominance hierarchies, but only in female crabs and not males (Gabbanini, Gherardi & Vannini, 1995). Claw dimensions but not claw force was found to be an important predictor of ®ght outcome in symmetrical contests between lobsters Homarus americanus (Vye et al, 1997), however, in this study the lobsters were kept for differing lengths of captivity (up to 4 weeks).…”
Section: Discussionmentioning
confidence: 99%